Stephanie Dinkins (University of Michigan Press, 2023)
Stephanie Dinkins is renowned for her critical investigations into artificial intelligence and machine learning systems as they intersect race, gender, and our future histories. By using her training in documentary practices as a photo-based artist, she creates inclusive platforms for dialogue and action toward building technological ecosystems and datasets that are equitable, accessible, and transparent. Her immersive installations, community-based workshops, and public talks seek audience participation and engagement in a way that pushes the boundaries of new media and socially engaged art practices in the 21st century.